Rinjani National Park Visitor Center Sebagai Pendukung Pengembangan Pariwisata: bahasa indonesia - Ida Wayan Sastra Adinata; Ni Putu Ratih Pradnyaswari Anasta Putri; I Made Suniastha Amerta; I Wayan Wirya Sastrawan; Nyoman Ratih Prabandari (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Tourism in Indonesia, particularly in the Rinjani National Park (TNGR) in East Lombok Regency, West Nusa Tenggara, has significant potential but faces several challenges. These include a lack of comprehensive information and promotion centers, limited tourism activities to encourage local potential development, and low participation from the local community. To address these issues, this research aims to design the Rinjani National Park Visitor Center as an integrated information and promotion center, as well as tourist accommodation serving as a platform for empowering the local community. This project is located in the village of Sembalun Lawang, Sembalun District, East Lombok. The project aims to address the challenges in tourism sector development by creating a visitor center in East Lombok Regency as an integrated information and promotion facility in the Rinjani National Park (TNGR), through strategies such as increased promotion, tour package regulations, infrastructure development, and empowerment of local human resources. It is hoped that this new facility will increase tourist visits to TNGR. Additionally, it is expected to make a positive contribution to national tourism development and the welfare of the local community.